Meta-Analysis of Positive Psychotherapy Interventions for Parents of Children with Special Needs in Iran - Siadati Arani, Sayed Hossein; Ashori, Mohammad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of this research was to conduct a meta-analysis of positive psychotherapy interventions for parents of children with special needs in Iran.Method: This study determined the effect size of positive psychotherapy interventions for these parents by synthesizing the results of various studies. The data sources included the National Publication Database, the Academic Jihad Science Information Center, and the Noor Specialized Journals Database. Out of 18 studies, 12 met the inclusion criteria and were selected, utilizing a meta-analysis checklist as the research tool. The study was based on 348 samples and 12 effect sizes.Findings: The meta-analysis revealed that the effect size of positive psychotherapy interventions for parents of children with special needs is d = 1.19 (p = 0.05), which is considered high according to Cohen's scale. The highest effect size was reported by Rezaei Kalantari et al. (2019), with a d = 2.31, titled "Effect of positive psychotherapy on perceived stress and life purposes in mothers of children with autism," and the smallest effect sizes were found in the study by Nili et al. (2019), with d = 0.2 and d = 0.23, titled "Effectiveness of positive training on irrational beliefs and happiness in mothers of deaf children."Conclusion: Overall, the results indicate that positive psychotherapy interventions are effective for parents of children with special needs, and researchers can utilize this program to enhance mental health components.